Developmental validation of the Investigator Argus Y-28 QS Kit. (December 2022) - Vraneš, Miroslav; Scherer, Mario; Cornelius, Stefan; Willuweit, Margaretha; Kraemer, Melanie; Terramagra, Daniele; Kohns, Annika; Prochnow, Anke
Abstract: The analysis of Y-chromosomal STRs is an integral part of forensic practice, especially in the context of sexual offenses, where it enables the identification of a male even in a high background of female DNA. We have developed and validated the new Investigator Argus Y-28 QS Kit as an assay to co-amplify 27 Y-STR markers. The new Fast Reaction Mix 3.0 ensures not only robust and fast PCR amplification with improved inhibitor resistance and easy handling, but also provides enhanced robustness towards DNA overloading and stability. Highly sensitive, yielding rapid and reliable results from trace DNA, the kit is suitable for all forensic applications. It can also be used for direct amplification of reference samples like blood or saliva on FTA cards or crude lysates from buccal swabs. Furthermore, the assay uses a 6-dye technology to keep the amplicon length of the markers short and to avoid marker overlap. The kit contains QIAGEN's Quality Sensor System (QS1 and QS2) as an internal PCR control.